Hanges in landscape transformation and land cover in the Hanság over the 18th-20th centuries - Takács, Gábor (JOURNAL OF LANDSCAPE ECOLOGY, 2011)
In the course of the planning phase of restoration and other conservation works increasingly popular in the past few years the history of the landscape to be rehabilitated has proven to be of crucial importance.During landscape history research besides the formerly used, mainly literary and archival resources geographic information system (GIS) processing of historical maps (I., II. and III. type military survey) is gaining ground. The maps processed with the unified methodology of GIS make it possible to compare the land cover and land use of various periods and to monitor the changes.Besides the river-regulations in Hungary, one of the most significant land transformations was the draining of Hanság. As a result of the works commenced in the 18th century, one of the largest marshlands and swamps of Hungary was practically destroyed or transformed entirely. My objective was to describe the characteristics of the ancient Hanság, the extent of the main types of land cover and land use practices predominant in the past 200 years. To study land transformation works, maps of six periods (1782-1784, 1840-1847, 1872-1880, 1920-1921, 1951, 1998) were processed. Land use and other mapped information was directly interpreted and digitized on a computer screen. Land cover patches, the road and watercourse system as well as punctiform objects were digitized in separate phases.The two most significant factors affecting the transformation of the Hanság landscape were draining and afforestation. In the 19th century, meadow and pasturage utilization increasingly gained ground in the inner areas that were aridifying due to draining, and, in line with it, former basin-edge grasslands and forests were ploughed. During this process open water surfaces, as well as marshland and swamp habitats disappeared and were displaced by bogs, marshy meadows and sedge-beds. As a result of further aridification and the diminished demand for hay, large-scale afforestation was commenced, which peaked in the creation of Populus cultures after World War II. Today the Hanság is covered by forestland (plantations), natural and semi-natural forests and arable land interspersed with remnants of various sized reed beds, sedge-beds, shrublands, boggy and marshy meadows.
Keywords: land cover; historical maps; nature conservation; habitat-restoration; GIS